Parental Involvement and Mathematical Proficiency Among Senior High School Students - Jhon Lawrence G. Detomal; Ludiemer C. De Manuel; Earl Ray C. Usman; Retchelle Sangco (International Journal of Research in Mathematics Education, 2026)
Parental involvement is widely recognized as a crucial factor in students’ educational outcomes, yet its specific influence on mathematical proficiency remains contested. This study investigated the levels of parental involvement and mathematical proficiency among 210 Senior High School STEM students from public schools in Digos City, Philippines, and examined the relationship between these variables. Using a descriptive–correlational design, parental involvement was measured through three indicators—school works, class works, and parental guidance and support—while mathematical proficiency was assessed across five domains: number sense, algebra, geometry, measurement, and data analysis, based on the NAEP framework. Results revealed high overall parental involvement, particularly in school works and guidance, but students’ mathematical proficiency remained at the beginning level, with the lowest performance in data analysis. No significant overall correlation emerged between parental involvement and mathematical proficiency, though a positive relationship was found between parental engagement in school works and performance in data analysis. These findings suggest that while general parental support may not directly enhance overall mathematics achievement, targeted involvement in specific learning tasks can positively influence particular areas of mathematical learning. Implications for parent-focused instructional support are discussed.